g-closed sets in ideal topological spaces
Characterizations and properties of I_g -closed sets and I_g -open sets are given. A characterization of normal spaces is given in terms of I_g -open sets. Also, it is established that an I_g -closed subset of an I-compact space is I-compact., number=3, journal=Methods of Functional Analysis and Topology, author=Antony Rex Rodrigo, J. and Ravi, O. and Naliniramalatha, A., year=2011, month=Sep., pages=274–280